Efecto inmunomodulador del SLPI en trasplante renal - Roteta Rocamora, Julia (2016)
Kidney transplantation is a therapeutic procedure that has made possible to prolong life of\nindividuals with chronic renal dysfunction. However, even today graft survival is not possible\nwithout a patient under immunosuppressive treatment, modifies the homeostasis of the\nimmune system, jeopardizing patient's life. That´s why strategies to evaluate patient's\nimmune status are required. The aim of this work was to study the role of an inhibitor of\nserine proteases called SLPI in renal transplant patients, with the intent to determine if this\nparameter could be useful as an indicator of immune status of the immunosuppressed\npatient. The results indicated that renal transplant patients have elevated levels of serum\nSLPI compared with healthy individuals. However, these levels were lower compared to\nthose seen in patients in pre-transplantation. Furthermore, immunosuppressive therapy\ninfluences SLPI levels as patients treated with mycophenolate mofetil + rapamycin +\nsteroids have higher levels patients treated with mycophenolate mofetil + steroids +\ntacrolimus. As expected, the proliferative capacity of mononuclear leukocytes in response to\na mitogen was lower in immunosuppressed patients compared to healthy individuals.\nHowever, treatment of cells in vitro with SLPI produced a decrease in cell proliferation\ninduced by a mitogen, in both groups of individuals (healthy and immunosuppressed).\nInterestingly, those individuals with higher plasma levels of SLPI had lower rates of cell\nproliferation, but correlated with reduced renal function. Overall, these results indicate that\nSLPI is a marker of renal damage with an immunomodulatory capacity. Its possible use as a\nmarker of immunosuppressive state must be validated with a larger number of individuals\nand likely will depend on the immunosuppressive therapy in progress by that time.